A Dataset for Toponym Resolution in Nineteenth-Century English Newspapers. (24th January 2022) - Coll Ardanuy, Mariona; Beavan, David; Beelen, Kaspar; Hosseini, Kasra; Lawrence, Jon; McDonough, Katherine; Nanni, Federico; van Strien, Daniel; Wilson, Daniel C. S.
We present a new dataset for the task of toponym resolution in digitized historical newspapers in English. It consists of 343 annotated articles from newspapers based in four different locations in England (Manchester, Ashton-under-Lyne, Poole and Dorchester), published between 1780 and 1870. The articles have been manually annotated with mentions of places, which are linked—whenever possible—to their corresponding entry on Wikipedia. The dataset consists of 3, 364 annotated toponyms, of which 2, 784 have been provided with a link to Wikipedia. The dataset is published in the British Library shared research repository, and is especially of interest to researchers working on improving semantic access to historical newspaper content.